Optimizing catheter ablation of atrial fibrillation by a novel wide-band dielectric imaging system: first experience on real-time wall thickness measurement. (19th May 2022) - Rottner, L; Moser, F; Schleberger, R; Moser, J; My, I; Lemoine, M; Dinshaw, L; Kirchhof, P; Ouyang, F; Reissmann, B; Metzner, A; Rillig, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Conventional mapping systems do not provide wall-thickness data, which is, however, known to be a determinant of radiofrequency ablation lesion transmurality. KODEX-EPD is a novel open-platform system, which uses dielectric tissue properties to provide real-time, high-resolution cardiac images, tissue characteristics and wall-thickness measurement to guide ablation procedures. Aim: The aim of this case series was to report on our first experiences with KODEX-EPD regarding estimation of myocardial wall-thickness during catheter ablation of atrial fibrillation (AF). Methods: We retrospectively analyzed consecutive patients undergoing radiofrequency AF-ablation in combination with KODEX-EPD. A high-resolution image from the left atrium (LA) and the pulmonary veins (PV) was obtained prior to ablation using a spiral mapping catheter in conjunction with KODEX-EPD. Wall-viewer points were collected within the LA, the PVs and the left atrial appendage (LAA) using a standard radiofrequency non-contact force ablation catheter and analyzed for wall-thickness applying the latest KODEX-EPD software version (1.5.0, not yet commercially released). Wall-viewer points were divided into a total of 10 segments (PV ostia, anterior wall, posterior wall, LA roof, LA floor, LAA and PV carina, details see Figure 1) in order to characterize wall-thickness in respective areas. Results: A total of 570 wall-viewer points in 5 patients were analyzed. Most of the wall-viewer points were collected at the PV ostia as well as along the posterior and anterior wall (449/570, 79%). Actual myocardial atrial thickness ranged from 1.6 to 3.9 mm. Thickest myocardial LA-tissue was measured at the anterior wall (median 3.1 mm) and thinnest at the LA-roof (median 2.2 mm). Figure 2 gives a detailed distribution of wall-thickness measurements at different sites in the LA and PVs. Conclusion: Atrial wall thickness can be estimated in patients during AF ablation procedures using dielectric tissue properties. Further evaluation and validation of the method are needed to study its reliability and utility for clinical practice.